Building the SHAKTI Microprocessor. - VEEZHINATHAN, KAMAKOTI (Communications of the ACM, 2022)
The article focuses on the development of the SHAKTI Processor Program, which aims to create microprocessors and microcontrollers within India. The author explains that SHAKTI is an open source processor and it started as an academic initiative by the Pratap Subramaniam–Center for Digital Intelligence and Secure Hardware Architecture (PC-CDISHA)–Reconfigurable Intelligent Systems Engineering (RISE) group, IIT-Madras.